Skyline tension and dynamic loading for cable yarding comparing conventional single-hitch versus horizontal double-hitch suspension carriages. (26th July 2021) - Spinelli, Raffaele; Magagnotti, Natascia; Cosola, Giulio; Grigolato, Stefano; Marchi, Luca; Proto, Andrea Rosario; Labelle, Eric R.; Visser, Rien; Erber, Gernot
ABSTRACT: Wire rope used in cable logging, where a series of cables facilitate the extraction of timber on steep terrain, experiences high tensions that must be managed to ensure safety. Innovations change practices over time and double-hitch carriages, which allow trees to be extracted horizontally, are a recent example. This makes it feasible to harvest across terrain with limited deflection, increases the recovery of biomass, and potentially reduces high-dynamic load events associated with ground contact. In this study, a standard single-hitch carriage was compared against a new double-hitch carriage under controlled conditions. Tension was measured continuously and specific elements, such as tension when the carriage was at midspan, maximum tension at breakout and inhaul, and magnitude of cyclic tension during inhaul were identified, measured and compared against payload. While payload was similar in the treatments, the additional weight of the double-hitch carriage resulted in higher skyline tensions. In both treatments, payload and skyline tension when the carriage was at midspan were strongly correlated. Cyclic tension was reduced by the double-hitch carriage system. While a number of unique high-dynamic loads were identified that were not part of the normal extraction, they represented only 6% of the cycles and the maximum tension was similar to that experienced during break-out and inhaul. This study increased the understanding of skyline tension during logging operations and the effect of carriage type. It showed that, though tension often exceeds the safe working load of the cable, it does not exceed the endurance limit for a well-designed and operated system.